Regionalization of benthic hard-bottom communities across the Pourtalès Terrace, Florida. (June 2021) - Walker, Brian K.; Messing, Charles; Ash, Jana; Brooke, Sandra; Reed, John K.; Farrington, Stephanie
Abstract: The Pourtalès Terrace is an exposed hard-bottom platform located south of the Florida Keys in 200–450 m depth with a diverse deep-sea coral ecosystem dominated by stylasterid hydrocorals, octocorals, and sponges that supports recreational and commercial fisheries. Portions of the Terrace have been designated as managed areas in the absence of detailed habitat maps, which hampers identifying ecological benefits derived from such management actions. Here we report analyses of historic Terrace physiographic and geologic data with more recent high-resolution bathymetric and benthic data to statistically derive a benthic community characterization across the Terrace. Multivariate analyses of faunal density from 42 standardized sites showed spatially distinct communities: East Terrace, West Terrace, Upper Terrace Edge, Sinkholes and Lophelia Coral Mound (the southernmost record of this habitat in the continental U.S.). These corresponded to physiographic divisions into an Upper Terrace comprised of Central and Karst-like regions, and Lower Terrace. A detailed description of these communities is provided. This study presents new insights into the Terrace benthic community spatial arrangement and is a necessary step towards facilitating benthic mapping. Our recommendations highlight the information needed for benthic habitat map creation and collecting data to determine if current conservation boundaries match management goals.